Hydrogen Production from Methanol Steam Reforming over Fe-Modified Cu/CeO2 Catalysts - Grzegorz Słowik; Marek Rotko; Janusz Ryczkowski; Magdalena Greluk (Molecules, 2024)
Fe-modified Cu catalysts with CeO2 support, prepared by the impregnation method, were subjected to physicochemical analysis and catalytic tests in the steam reforming of methanol (SRM). Physicochemical studies of the catalysts were carried out using the XRF, TEM, STEM-EDS, XRD, TPR and nitrogen adsorption/desorption methods. XRD, TEM studies and catalytic tests of the catalysts were carried out at two reduction temperatures, 260 °C and 400 °C, to determine the relationship between the form and oxidation state of the active phase of the catalysts and the catalytic properties of these systems in the SRM. Additionally, the catalysts after the reaction were analysed for the changes in the structure and morphology using TEM methods. The presented results show that the composition of the catalysts, morphology, structure, form and oxidation state of the Cu and Fe active metals in the catalysts and the reaction temperature significantly impact their activity, selectivity and stability in the SRM process. The gradual deactivation of the studied catalysts under SRM conditions could result from the forming of carbon deposits and/or the gradual oxidation of the copper and iron phases under the reaction conditions.